Determination of Arsenic in Aqueous Samples by Kinetic Fluorescence - Zhu, R.H.; Chen, L.H. (Asian Journal of Chemistry, 2011)
A simple and selective method is described for the determination of arsenic(III) by kinetic fluorometry. The fluorescence intensity of pyronine B is decreased by adding some KIO3. However, the fluorescence intensity of pyronine B is further decreased with the presence of arsenic(III), because the pyronine B oxidation by KIO3 with arsenic(III) as catalyst was formulated in sulfuric acid medium. There is a good linearity between the fluorescence intensity of pyronine B and the concentration of arsenic(III). The method allows for the determination of arsenic(III) in the range from 2.0-300 μg/L and the limit of detection is 1.4 μg/L. It has been successfully applied to the determination of arsenic(III) in real samples and the RSD is 2.4 % at 100 μg/L arsenic(III) (n = 11).